A study on circulation strength decay over time of quadrotor wake using Large Eddy Simulation - Nathanael, Joshua Christian (2022)
As the use of multi-rotors is becoming common, understanding how the wake vortices develop and decay from a multi-rotor is important to reduce the effect of wake vortices on other multi-rotors and ensure their safety during operation by applying a wake separation minima. This paper proposes a method of flow simulation in ANSYS Fluent to study the decay of wake vortices from quadrotor propellers as the vortices evolve over distance and time. First, the near-field wake flow from the quadrotor propellers was simulated using Reynolds-Averaged Navier-Stokes (RANS) turbulence model. The velocity profile in the quadrotor frame of reference was then extracted to be applied for a flow simulation using Large Eddy Simulation (LES). The circulation strength as a function of distance could then be calculated, but it was limited by the length of the computational grid due to the wake flow being seen from the quadrotor frame of reference. To change into the stationary frame of reference, the interpolation data from the first stage LES was exported and modified by subtracting the freestream velocity from the velocity component in the freestream direction. The modified interpolation data was then used for the second stage LES, and the circulation strength in terms of time could be calculated from the resulting wake flow. Three cases of flow simulation are presented in this paper: first using 380-mm-diameter propellers based on the SUI Endurance quadrotor propellers with forward flight speed of 6 m/s, second using the 380-mm-diameter propellers with 12 m/s speed, and third using 240-mm-diameter propellers (similar to the propellers of DJI Phantom quadrotor) with 12 m/s speed. Findings regarding the decay of wake vortex from multi-rotor vehicles will help in determining the safe separation distance required to mitigate the hazards due to wake vortex encounters and ensure the safety of multi-rotor vehicles.